Identifying Different Halogen‐/Hydrogen‐Bonding Interaction Modes in Binary Systems that Contain an Acetate Ionic Liquid and Various Halobenzenes. Issue 9 (27th February 2018) - Xu, Jing; Zhou, Yu; Deng, Geng; Ashraf, Hamad; Yu, Zhi‐Wu
Abstract: Elucidation of the nature of noncovalent interactions between ionic liquids (ILs) and halogenated molecules is of particular importance for both fundamental research and drug development. Herein, the noncovalent interactions between 1‐butyl‐3‐methyl‐imidazolium acetate and three halobenzenes C6 F5 X (X=I, Br, H) were investigated. The iodine derivative shows the strongest interaction with the IL, followed by C6 F5 Br and C6 F5 H. As indicated by the positive/negative peaks and "multi/two‐state" phenomena in the excess IR spectra, combined with DFT calculations, various interaction modes were differentiated. Three complexes, namely anion–C6 F5 I, anion–2 C6 F5 I, and ion‐pair–C6 F5 I in the IL–C6 F5 I system were identified, whereas only ion‐pair–C6 F5 Br/C6 F5 H complexes, together with self‐associates, were found in the other two systems. A possible reason for the behavior of the IL–C6 F5 I system could be that the iodine‐based halogen‐bonding interactions in the system are strong enough to break interactions between the IL cations and anions. This might make C6 F5 I a good co‐solvent to regulate the properties of acetate‐based ILs. Abstract : Exploring interactions : The "multi/two‐state" phenomena, indicated by the shifted/fixed positions of excess IR peaks, provide information on the solution structure. Combined with DFT calculations, some species and different interaction modes in three ionic liquid/halobenzene systems are identified. The characteristics of the interaction modes are discussed with respect to the halogen‐ and hydrogen‐bonding interaction strength.